2020
DOI: 10.1016/j.aquatox.2020.105541
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of nano-TiO2 and hexavalent chromium towards marine crustacean Artemia salina

Abstract: There has been a significant increased concern of the impact of the toxicity of multiple contaminants in the marine environment. Thus, this study was aimed at determining whether the interaction between nano-TiO 2 and Cr(VI) would modulate their toxic effects with the marine crustacean, Artemia salina. Nano-TiO 2 agglomerated in artificial sea water (ASW) and readily formed micron-sized particles that settled down in the medium. The addition of Cr(VI) to nano-TiO 2 aggravated their agglomeration through sorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 46 publications
(47 reference statements)
1
21
0
Order By: Relevance
“…Pristine TiO2 NPs induced dose-dependent acute toxicity in A. salina, which was in line with the previous findings of Thiagarajan et al (2020). Accumulation of TiO2 NPs in the gut is considered as one of the mechanisms by which TiO2 NPs may induce mortality in A. salina.…”
Section: Waterborne Exposure Effects To a Salinasupporting
confidence: 91%
“…Pristine TiO2 NPs induced dose-dependent acute toxicity in A. salina, which was in line with the previous findings of Thiagarajan et al (2020). Accumulation of TiO2 NPs in the gut is considered as one of the mechanisms by which TiO2 NPs may induce mortality in A. salina.…”
Section: Waterborne Exposure Effects To a Salinasupporting
confidence: 91%
“…To date, nano-ecotoxicity studies evaluating the acute effects of NPs on crustaceans at the molecular level have mostly considered gene expression related to antioxidant enzymes such as Sod, catalase, GPx and glutathione S-transferase (Kim et al 2010, Clemente et al 2014, Kögel et al 2020). Recently, Thiagarajan et al (2020) showed that n-TiO 2 caused reduced Sod activity in Artemia salina . It is well known that n-TiO 2 increases ROS production and could activate antioxidant defence mechanisms such as Sod and GPx to protect cells from oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The combined toxicity of NPER and PSNPs was validated by using an independent action model (Table 2). When a PSNP concentration of 100 mg L −1 and NPER concentration of 2 mg L −1 were combined, the R I values was observed to be decreased below 1, 27 proving their antagonistic on Artemia salina. However, when the concentration of NPER was increased from 4 to 32 mg L −1 , the complex exhibited synergistic effects on the organisms.…”
Section: Papermentioning
confidence: 97%
“…The absorbance of the reaction mixture at 560 nm was measured using a microplate reader -BIORAD. 27 The most widely used technique for studying lipid peroxidation in biological systems is the malondialdehyde (MDA) assay, which measures thiobarbituric acid-reactive compounds (TBARS) by the thiobarbituric acid (TBA) test. 28 As a gauge of oxidative stress, TBARS were evaluated to ascertain the lipid peroxidation products.…”
Section: View Article Onlinementioning
confidence: 99%